A New Solution Approach for UAV Routing Problem with Moving Target - Heterogeneous Fleet - Ucar, Ukbe Usame; Isleyen, Selcuk Kursat (Gazi Univ, 2019)
The technological developments in the defence industry lead countries to create unmanned armies based on robotic systems. Due to the intense use of unmanned aerial vehicles in the instant surveillance, tracking, detection and disposal of targets, it is an important and difficult problem to determine which of the different types of air vehicles in the field of operations should be selected and how they can be effectively routed. In this study, a multi-criteria solution approach based on heuristic algorithm is proposed for destroying moving targets taking into account of the capacity and time window constraints by armed and unarmed unmanned aerial vehicles moving as a fleet. The Analytical Hierarchical Process method was used to prioritize the targets and pursuers; and it was aimed to destroy all targets with a minimum number of vehicles in a short time due to the cost of flights with UAVs, increase in maintenance-repair costs and the risk of fault due to unnecessary UAV use, the use of large numbers of UAVs in the field of operation evoked enemy elements and directed them to take defensive measures against UAVs. The effectiveness of the algorithm has been tested on 25 different scenarios where the number of pursuers is between 10 and 50 and the target number ranges from 40 to 200. As a result, it has been determined that all targets are destroyed with minimum number of vehicles according to the specified order of priority within the acceptable solution period and the proposed method contributed to the efficient routing of (heterogeneous) unmanned aerial vehicles moving in a fleet.
Keywords: Dynamic unmanned aerial vehicle routing problem; analytical hierarchical process; heuristic algorithm; moving target traveling salesman problem; fleet routing